Microencapsulación de un extracto de eneldo (Anethum graveolens) mediante secado por aspersión - Pacheco Párraga, Claudia Nohelia (2022)
A microencapsulated extract of dill (Anethum graveolens) was elaborated, through the unitary operation of spray drying, using maltodextrin and gum arabic as materials for the encapsulation, the same ones that serve as a method of protection of the active principles of interest, preventing its degradation. The benefits of dill extract were preserved, being resistant to environmental factors, and maintaining its physicochemical characteristics. Through a previous analysis, the analyzes carried out, the parameters and the specific applicable methodologies were selected. According to the established independent variables, inlet air temperature and feed flow rate, 13 experimental runs were carried out, with ranges from 130 °C to 150 °C and from 500 ml/h to 700 ml/h, respectively. For the experimental design, the Design Expert 8.0.6 program was obtained to facilitate modeling based on the data obtained. Finally, the process is optimized where the best drying conditions are: TAE of 150 °C and VFA of 500 ml/h. With these measurements, the optimal data of yield, humidity and efficiency of the microencapsulation are expressed, these being 89,23 %, 2,29 % and 88,23 %, respectively. In addition, the characterization of the microencapsulation allows expressing the results for: hygroscopicity 17,32 g/100 g, bulk density 0,35 g/ml, compacted density 0,62 g/ml, angle of repose 33,69, solubility 62,06 %, Hausner index 1,75, Carr index 43,02 %, iron-reducing antioxidant capacity (FRAP) 678,12 (µM Fe2+ /g sample). This information is supported by laboratory tests, and related in turn to different academic sources.